Renin-angiotensin system and idiopathic pulmonary fibrosis: What is the link? - Perin, Fabíola Adélia; Silveira, Andresa Thomé; Silva, Laura Tibola Marques da; Rigatto, Katya (Seven Editora, 2024)
Interstitial lung diseases comprise a heterogeneous group of non-neoplastic diseases with varying degrees of inflammation and/or fibrosis. Some with known causes, others with varied etiologies that are not always identified, the so-called idiopathic interstitial pneumonias. Among them, idiopathic pulmonary fibrosis (IPF), considered a prototypical fibrotic disease1,2. IPF is a non-neoplastic progressive lung disease with different degrees of inflammation and fibrosis, the clinical manifestation of which is progressive dyspnea. The etiology and pathophysiological mechanism of the disease are quite complex and not fully understood, hindering effective therapeutic alternatives. Evidence in the literature demonstrates the involvement of Angiotensin II (Ang II), the most studied vasoactive peptide of the renin-angiotensin system involved in the pathogenesis of fibrosis. In this context, it is possible to believe that the imbalance of the Renin-Angiotensin System (RAS) in favor of the fibrosing axis (Ang II/AT1) is associated with the development of pulmonary fibrosis (PF) and functional impairment of patients. On the other hand, the counter-regulatory and protective axis of the RAS, the peptides Angiotensin 1-7 and Alamandin, may be an alternative treatment of PF. Therefore, new interpretations of the participation of this system in the pathophysiology of IPF may contribute to elucidate the mechanisms involved in this disease, which still has no cure, which is highly costly for the health system and especially for the development of therapies that improve the quality of life of these patients. DOI:https://doi.org/10.56238/interdiinovationscrese-094